EXPERIENCE IN THE CORRECTION OF THE INTESTINE MICROBIOTADYS DYSBALANCE ON THE BACKGROUND OF SECONDARY LACTASE DEFICIENCY - L.A. Tarasova; V.N. Danilova; L.N. Voronina (Педиатрическая фармакология)
One of the main conditions for normal growth and development of the child is a full-grown digestion. In this paper, the authors emphasize the importance of the intestinal microbiota condition for adequate digestion, and they are citing the main causes of disaccharidase deficiency, which contributes to the violations of the microbiota and exacerbates the intestine damage. Scientists share their experience of the correction of biocenosis and functional intestines disorders in infants.Key words: digestion, intestinal microbiota, biologics, intestine biocenosis violations, correction, children.